2005
DOI: 10.1088/0741-3335/47/11/007
|View full text |Cite
|
Sign up to set email alerts
|

Electron heat transport in shaped TCV L-mode plasmas

Abstract: Electron heat transport experiments are performed in L-mode discharges at various plasma triangularities, using radially localized electron cyclotron heating to vary independently both the electron temperature T e and the normalized electron temperature gradient R/L T e over a large range. Local gyrofluid (GLF23) and global collisionless gyro-kinetic (LORB5) linear simulations show that, in the present experiments, trapped electron mode (TEM) is the most unstable mode. Experimentally, the electron heat diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 37 publications
4
35
0
Order By: Relevance
“…Gyro-kinetic stability analysis indicated that the TEM are the dominant modes [21]. Similar experiments repeated in DIII-D [33] and TCV [34] yielded comparable results.…”
Section: Perturbative Heat Transport Results In L-and H-mode Plasmas supporting
confidence: 52%
“…Gyro-kinetic stability analysis indicated that the TEM are the dominant modes [21]. Similar experiments repeated in DIII-D [33] and TCV [34] yielded comparable results.…”
Section: Perturbative Heat Transport Results In L-and H-mode Plasmas supporting
confidence: 52%
“…16 Experimental evidence for profile stiffness and critical gradients is also found in several tokamaks. [17][18][19][20][21][22][23] As a consequence of stiff transport in the plasma core, the edge temperature provides the key boundary condition dictating overall plasma performance. 10,14,24 This means that in very stiff core plasmas, like many H-modes, small decreases/increases in local temperature gradients can lead to large decreases/increases in local diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect evidence supporting the existence of critical gradients has been reported in tokamaks for both electron and ion thermal transport. [2][3][4][5][6] Validation for the existence of critical gradients in fusion experiments requires direct, local measurements of the fluctuations that are driving the transport. Direct, systematic observation of instability has been related to critical gradient criteria in linear experiments; 7-9 however, no previous work exists in the core of a confined high-temperature plasma.…”
Section: Introductionmentioning
confidence: 99%